Control of Vibrio sp. Through the addition of the Probiotic Microbial Consortium (Halomonasalkaliphila, H. aquamarina, and Bacillus cereus), Nitrifying Bacteria and Chaetoceeros sp. in White Shrimp (Litopenaeusvannamei) with ZWD (Zero Water Discharge) System. - Nada Bakri, Sara
Vibriosis can reduce growth and cause death in shrimp which causes huge losses for shrimp farmers. One agent that generally causes vibriosis is Vibrio harveyii when its density reaches the quorum (106 CFU / ml). Generally, shrimp farmers use antibiotics and drugs to prevent vibriosis. Currently the use of antibiotics and drugs have been banned in shrimp farming. Therefore another solution is needed to regulate Vibrio sp., one of them by using microbial consortium. This study uses a microbial consortium consisting of three probiotic bacteria (Halomonas alkaliphila, H. aquamarina, and Bacillus cereus), nitrifying bacteria (Nitrosococcus sp. and Nitrobacter sp.), and algae Chaetoceros sp. This research was conducted with the aim of determining the effect of microbial consortium on growth and survivability of shrimp, also the total number of Vibrio sp. in the challenge test and grow-out using the ZWD system. In general, this study consists of two stages: (1) challenge test of microbial consortium with V. harveyii on 5-day –old shrimp larvae (PL5) nursery using six treatment variation: control without addition of microbial consortium and V. harveyii (P1) , control positive by addition of microbial consortium (density 106 CFU/ml for each probiotic microbial species) (P2), control negative with the addition of V. harveyii (density 106 CFU / ml) (P3), addition of microbial consortium and V. harveyii at the same time (P4), addition of microbial consortium 24 hour before addition of V. harveyii (P5), and addition of microbial consortium 24 hour after addition of V. harveyii (P6); (2) white shrimp grow-out using ZWD (Zero Water Discharge) system with 4 treatment variations: addition of microbial consortium (density 103 CFU / ml for each probiotic species) (A), addition consortium 24 hours before addition of V. harveyii ( density 103 CFU/mL) (B), with the addition of V. harveyii (C), control without the addition of microbial consortium and V. harveyii (D). Based on the results of the study, in the challenge test the highest survivability level of shrimp was P5 (50.00 ± 1.82%), followed by P6 (46.46 ± 2.32%) and P4 (43.02 ± 1.07%) which were significantly different with negative control (P3) (42.26 ± 1.15%) (p <0.05) and not significantly different from control (P1) (57.79 ± 1.78%) and positive control (P2) ( 62.1 ± 6.35%) (p> 0.05). Furthemore, in P4, P5, P6 and control positive (P2) total Vibrio sp. decrease so that lower than total Vibrio sp. in control negative (P3). At the shrimp grow-out, obtained the mean body weight (MBW) of shrimp from highest to lowest are: A (4.30 ± 2.20 g), D (3.73 ± 1.46 g), B (3.57 ± 1, 39 g), and C (0.73 ± 0.20 g). MBW in treatment B was significantly different (p <0.05) from control negative and not significantly different (p> 0.05) from control (C) and control positive (A). Furthermore, the survivability of treatment A, B, C, and D did not differ significantly. Total Vibrio sp. in treatment A, B, and D is stable in the amount of 102-105 CFU/ml. Whereas in shrimp, total Vibrio sp. in treatment A and B controlled lower than 106 CFU / gram of shrimp. Based on the results of the study, it can be concluded in the challenge test, addition of microbial consortium 24 hours before addition V. harveyii (P5) can decrease the number of Vibrio sp. in water and control the amount of Vibrio sp. on shrimp lower than 101 CFU / gram so that can increasing te survivability of white shrimp. At the white shrimp grow-out, addition of microbial consortium 24 hours before addition V. harveyii (P5) can increasing shrimp growth but can’t increasing the survivability of shrimp, also can control the total Vibrio sp. in water and shrimp at density lower than lethal dose (106 CFU/ml).